VD_FINDINFO Jug / 2017 / 19 vom 2. Mai 2017 - VD Tribunal cantonal (2017)
PRÊT DE CONSOMMATION, DONATION, RESTITUTIONEN GÉNÉRAL, INTERPRÉTATIONSENS GÉNÉRAL, SOCIÉTÉ SIMPLE | 728 al. 1 CC, 1 CO, 11 CO, 2 CO, 239 CO, 249 ch. 1 CO, 312 CO, 313 CO, 314 CO, 318 CO, 1 al. 1 LDIP, 1 al. 2 LDIP, 116 LDIP, 117 LDIP, 5 LDIP, 6 al. 1 LDIP